Beauty Concept In Sephora’s “Black Beauty Is Beauty” Campaign Video - Kalalo, Elizabeth Octovianne; Perdana, Abhirama S.D. (Expose: Jurnal Ilmu Komunikasi, 2024)
The dominance of Western beauty standards has often marginalized and rejected Black bodies and beauty in mainstream culture. However, Black communities have significantly contributed to the beauty industry. In response to this disparity, Sephora, a leading beauty retailer, launched a campaign to combat racial inequity by promoting Black-owned beauty brands. The campaign features a short video titled Black Beauty is Beauty, which highlights Black narratives, cultural practices, and the historical influence of Black beauty innovations on global beauty standards. This study examines how Sephora portrays beauty concepts in its campaign video. A qualitative method with purposive sampling is employed for data collection. Social semiotics and visual grammar serve as the theoretical frameworks, as they analyze both visual and spoken texts. The findings reveal several categories of beauty representation in the campaign video, including physical appearance, beauty traits, beauty routines, and gendered beauty—elements historically overlooked by mainstream culture. Through these representations, Sephora reintroduces Black beauty ideals, emphasizing their impact on shaping beauty trends. The campaign also challenges conventional beauty standards, such as fair skin, straight hair, and thin body types, which contrast with African physical characteristics.